Complex families, the social determinants of health and psychosocial interventions: Deconstruction of a day in the life of hospital social workers. (14th September 2017) - Muskat, Barbara; Craig, Shelley L.; Mathai, Biju
ABSTRACT: The roles of hospital social workers are delineated in the literature; however, their daily interventions have only been described anecdotally. This study analyzes the daily work of social workers in a pediatric hospital through a survey completed which examined factors related to interventions utilized and time spent per case over a 1-day period. Length and types of interventions were associated with the social determinants of health, time since diagnosis, biopsychosocial issues, and perception of complexity. The study offers a snapshot of the personalized expertise, provided by social workers that addresses complex contextual and biopsychosocial concerns of patient and families